Smoking and Coronary Atherosclerosis: Disproportionate Impact on the Right Coronary Artery - Dahlgren, Axel; Erlinge, David; Torii, Ryo; Yong, Enhui; Bergström, Göran; Jernberg, Tomas; Fröbert, Ole; Thrane, Pernille G.; Mæng, Michael; Stone, Gregg W.; Mohammad, Moman A. (JOURNAL OF THE SOCIETY FOR CARDIOVASCULAR ANGIOGRAPHY & INTERVENTIONS, 2025)
We aimed to study the long-term effect of smoking on coronary atherosclerosis progression at the segmental level. Angiographic data (1989-2017) on current, former, and nonsmokers were collected from the Swedish Coronary Angiography and Angioplasty Registry. The Western Denmark Heart Registry was used to validate the results. Patients with clinically indicated angiography with ≥2 coronary arteries without obstructive coronary artery disease were included. The main outcome was segmental plaque progression, percutaneous coronary intervention, or coronary artery bypass grafting within 15 years. In total, 215,364 Swedish patients with 993,405 coronary arteries (left anterior descending artery [LAD], left circumflex artery [LCX], and right coronary artery [RCA]) were included. The validation cohort consisted of 19,613 patients. Per 1000 patient-years, plaque progression incidence rate was 11.3 (95% CI, 10.9-11.7) for smokers, 10.2 (95% CI, 9.9-10.5) for former smokers, and 7.7 (95% CI, 7.5-7.9) for nonsmokers. Smokers demonstrated higher relative risk of plaque progression in RCA (hazard ratio, 1.87; 95% CI, 1.73-2.03) vs LAD (hazard ratio, 1.21; 95% CI, 1.12-1.30). Swedish and Danish smokers with ST-segment elevation myocardial infarction had higher proportion of RCA as the culprit artery compared to nonsmokers (smokers: RCA, 42.4%; LAD, 42.0%; LCX, 15.6%; nonsmokers: RCA, 33.1%; LAD, 51.4%; LCX, 15.5%). This observational cohort study identifies distinct differences in plaque progression patterns between smokers and nonsmokers, with smoking linked to increased plaque progression in the RCA, in contrast to the LAD in nonsmokers. These findings reemphasize the need for targeted smoking prevention and warrant further investigation into RCA-specific mechanisms of plaque progression and MI.